PENGEMBANGAN MEDIA PEMBELAJARAN COMIC LIFE PADA MATA PELAJARAN IPA KELAS V MIN 2 DHARMASRAYA - Tosi Husnulabsori; Yulia Darniyanti; Muhammad Subhan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Education is very important in human life, meaning that every human being deserves it and is expected to always develop in it, Education will never end. In this study, the author is interested in developing comic learning media. This research uses the type of research and development R&D (Reseasrch and Development). Based on the problems that have been described in the background, this study uses the ADDIE model (Analiyze, Design, Development, Implementation, Evaluation). The types of data taken in this study are qualitative data types and quantitative data Data collection techniques used by the author using Interview, Observation and Documentation techniques. Data analysis techniques carried out in writing this development are validity analysis, effectiveness analysis and practicality analysis. On the validation sheet, there are filling instructions and 3 aspects of assessment including aspects of language feasibility, design feasibility, and content / construction feasibility with average scores. The results of the practicality sheet design contain filling instructions and assessment aspects that will be assessed by educators and students. The results of the practicality sheet design contain filling instructions and assessment aspects that will be assessed by educators and students. The results of the validation design of the effectiveness sheet (learning outcome test) effectiveness there are filling instructions and aspects assessed by validators. In addition, the completeness of student learning outcomes with an average of 95% is categorized as very effective.